Вплив розташування автовокзалів на завантаженість вулично-дорожньої мережі міста - Пашкевич, Світлана (ТзОВ «Галицька видавнича спілка», 2021)
Alleviating public traffic congestion is an efficient and effective way to improve the travel time reliability and quality of public transport services. The existing public network optimization models usually ignored the essential impact of public traffic congestion on the performance of public transport service. To solve this problem, a data-based methodology is proposed to estimate congestion on road sections between bus stops.
The impact of the location of bus stations on the congestion of the city's road network
Keywords: 656.025